The Strengthen the Strategy of the "Dasawisma" food security program in Luwuk Tukau village - Alim, Bimantara Nur; Andreastuti, Desie (Journal Ilmu Sosial, Politik dan Pemerintahan, 2026)
Food security stands as one of the most pressing challenges in sustainable development, especially within rural settings where agriculture is the main source of sustenance. The Dasawisma initiative, launched under the auspices of the Family Welfare Empowerment (PKK), is vital in bolstering household-level food security. This research seeks to evaluate methods for enhancing the effectiveness of the Dasawisma food security initiative in Luwuk Tukau Village. Employing a qualitative descriptive methodology, this investigation explores both the facilitating and hindering factors affecting the program's execution. Results indicate that strong community engagement, governmental backing, and ongoing training are essential for the program's achievements. Nonetheless, barriers such as a lack of agricultural expertise, limited access to resources, and inadequate institutional backing continue to pose substantial challenges. This research offers strategic suggestions to enhance the efficiency and long-term viability of the Dasawisma program in fostering community-oriented food security within rural locales. Keywords: Dasawisma, food security, community empowerment